2017
DOI: 10.20344/amp.8835
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Portuguese Amateur Youth Football Players: A Six Month Prospective Descriptive Study

Abstract: This study provides descriptive data on injuries developed in a subpopulation of Portuguese amateur youth football players that could represent a focus for future prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…Differential bone growth (femur) in relation to muscle length can result in a decrease in flexibility (hamstring) and strength (De Ste Croix & Korff, 2013). In addition, these muscles have been the most studied muscle group by scientific literature, given that they represent one of the most injured areas in sport, in general, and soccer, in particular (Nogueira et al, 2017; Price et al, 2004). Several published injury prevention programs include hamstring dynamic or static stretching exercises in order to increase the flexibility in these muscles (DiStefano et al, 2009; Kiani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Differential bone growth (femur) in relation to muscle length can result in a decrease in flexibility (hamstring) and strength (De Ste Croix & Korff, 2013). In addition, these muscles have been the most studied muscle group by scientific literature, given that they represent one of the most injured areas in sport, in general, and soccer, in particular (Nogueira et al, 2017; Price et al, 2004). Several published injury prevention programs include hamstring dynamic or static stretching exercises in order to increase the flexibility in these muscles (DiStefano et al, 2009; Kiani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 In the past 2 decades, a number of prospective studies have been published describing the incidence and pattern of injuries in youth football players. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Recently, a systematic review combined and meta-analysed most of the injury incidences available for elite male youth football and reported overall injury rates of 7.9 and 3.7 time-loss injuries per 1000 h of exposure for players aged under (U) 17 to U21 (i.e., players from around age 17 to age 21) and U9 to U16 (i.e., players from around age 9 to age 16), respectively. 28 Furthermore, the same study proposed that a median of 18% (nearly one-fifth) of all reported injuries might be classified as severe (>28 days of absence), with muscle injuries accounting for 37% of all injuries sustained in elite male youth football.…”
Section: Introductionmentioning
confidence: 99%
“…Differential bone growth (femur) in relation to muscle length can result in a decrease in flexibility (hamstring) and strength (De Ste Croix & Korff, 2012). In addition, these muscles have been the most studied muscle group by scientific literature, given that they represent one of the most injured areas in sport, in general, and soccer, in particular (Nogueira, Laiginhas, Ramos, & Costa, 2017;Price, Hawkins, Hulse, & Hodson, 2004). Several published injury prevention programs include hamstring dynamic or static stretching exercises in order to increase the flexibility in these muscles (DiStefano, Padua, DiStefano, & Marshall, 2009;Kiani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%